Predictive numerical modeling of groundwater drawdown impacts in Jakarta - Iwan Nursyriwan; Muhammad Bisri; Lily Montarcih; Ery Suhartanto (Faculty of Geography, Universitas Gadjah Mada, 2019)
An excessive groundwater usage is happening in Jakarta, Indonesia, due to the population growth and industrial development so that it experiences a significant groundwater drawdown which could enhance the risk of seawater intrusion and land subsidence. Existing conditions in 2018 show that seawater intrusion occurred at the Western and Central coastal area and land subsidence happen in the Northern and Central part. This research, a numerical simulation, is conducted by modeling such causality during the critical period, the next 20 years. The result shows that for every groundwater drawdown of 10 m/year, it will cause intrusion 0.7 km/year in the Western and Central and 1.1 km/year in the Eastern area after 2028. The 10 m/year groundwater drawdown also results in land subsidence of 5.7 cm/year in the Northern and 2.5 cm/year in Central Jakarta. This result is useful as an input for groundwater management policies and to prevent the environmental impacts occurred at other large coastal cities.